Pharmacokinetics of tolfenamic acid in green sea turtles (Chelonia mydas) after intravenous and intramuscular administration. Issue 6 (10th June 2020) - Raweewan, Natsuda; Chomcheun, Thanaphan; Laovechprasit, Weerapong; Jongkolpath, Oranee; Klangkaew, Narumol; Phaochoosak, Napasorn; Giorgi, Mario; Poapolathep, Amnart; Poapolathep, Saranya
Abstract: The present study aimed to evaluate the pharmacokinetic features of tolfenamic acid (TA) in green sea turtles, Chelonia mydas. Green sea turtles were administered single either intravenous (i.v.) or intramuscular (i.m.) injection of TA, at a dose of 4 mg/kg body weight (b.w.). Blood samples were collected at preassigned times up to 168 hr. The plasma concentrations of TA were measured using a validated liquid chromatography tandem mass spectrometry method. Tolfenamic acid plasma concentrations were quantifiable for up to 168 hr after i.v. and i.m. administration. The concentration of TA in the experimental green sea turtles with respect to time was pharmacokinetically analyzed using a noncompartment model. The C max values of TA were 55.01 ± 8.34 µg/ml following i.m. administration. The elimination half‐life values were 32.76 ± 4.68 hr and 53.69 ± 3.38 hr after i.v. and i.m. administration, respectively. The absolute i.m. bioavailability was 72.02 ± 10.23%, and the average binding percentage of TA to plasma protein was 19.43 ± 6.75%. Based on the pharmacokinetic data, the i.m. administration of TA at a dosage of 4 mg/kg b.w. might be sufficient to produce a long‐lasting anti‐inflammatory effect (7 days) for green sea turtles. However, further studies are needed to determine the clinical efficacy of TA for treatment of inflammatory disease after single and multiple dosages.